Surgical Risk Assessment and Prevention in Elderly Spinal Deformity Patients. (20th May 2019) - Thomas, Kevin; Wong, Ka Hin; Steelman, Susan C.; Rodriguez, Analiz
Introduction: Prevalence of adult deformity surgery in the elderly individuals continues to increase. These patients have additional considerations for the spine surgeon during surgical planning. We perform an informative review of the spinal and geriatric literature to assess preoperative and intraoperative factors that impact surgical complication occurrences in this population. Significance: There is a need to understand surgical risk assessment and prevention in geriatric patients who undergo thoracolumbar adult deformity surgery in order to prevent complications. Methods: Searches of relevant biomedical databases were conducted by a medical librarian. Databases searched included MEDLINE, Web of Science, CINAHL, IPA, Cochrane, PQ Health and Medical, SocINDEX, and WHO's Global Health Library. Search strategies utilized Medical Subject Headings plus text words for extensive coverage of scoliosis and surgical technique concepts. Results: Degenerative scoliosis affects 68% of the geriatric population, and the rate of surgical interventions for this pathology continues to increase. Complications following spinal deformity surgery in this patient population range from 37% to 62%. Factors that impact outcomes include age, comorbidities, blood loss, and bone quality. Using these data, we summarize multimodal risk prevention strategies that can be easily implemented by spine surgeons. Conclusions: After evaluation of the latest literature on the complications associated with adult deformity surgery in geriatric patients, comprehensive perioperative management is necessary for improved outcomes. Preoperative strategies include assessing physiological age via frailty score, nutritional status, bone quality, dementia/delirium risk, and social activity support. Intraoperative strategies include methods to reduce blood loss and procedural time. Postoperatively, development of a multidisciplinary team approach that encourages early ambulation, decreases opiate use, and ensures supportive discharge planning is imperative for better outcomes for this patient population.